Effects of sodium restriction and hydrochlorothiazide on RAAS blockade efficacy in diabetic nephropathy: a randomised clinical trial - Kwakernaak, Arjan J; Krikken, Jan A; Binnenmars, S Heleen; Visser, Folkert W; Hemmelder, Marc H; Woittiez, Arend-Jan; Groen, Henk; Laverman, Gozewijn D; Navis, Gerjan (The lancet. Diabetes & endocrinology, 2014)
Reduction of dietary sodium intake or diuretic treatment increases renin-angiotensin-aldosterone system (RAAS) blockade efficacy in non-diabetic nephropathy. We aimed to investigate the effect of sodium restriction and the diuretic hydrochlorothiazide, separately and in combination, added to RAAS blockade on residual albuminuria in patients with type 2 diabetic nephropathy. In this multicentre, double-blind, placebo-controlled, crossover randomised trial, we included patients with type 2 diabetic nephropathy. Main entry criteria were microalbuminaria or macroalbuminuria, and creatinine clearance of 30 mL/min or higher with less than 6 mL/min decline in the previous year. We tested the separate and combined effects of sodium restriction (dietary counselling in the outpatient setting) and hydrochlorothiazide (50 mg daily), added to standardised maximal angiotensin-converting enzyme (ACE) inhibition (lisinopril 40 mg daily), on albuminuria (primary endpoint). Patients were given hydrochlorothiazide (50 mg per day) or placebo during four treatment periods of 6 weeks. Both treatments were combined with regular sodium diet or sodium restriction (target sodium intake 50 mmol Na+ per day). The 6-week treatment periods were done consecutively in a random order. Patients were randomised in blocks of two patients. The trial was analysed by intention to treat. The trial is registered with TrialRegister.nl, number 2366. Of 89 eligible patients, 45 were included in the study. Both sodium restriction and hydrochlorothiazide significantly reduced albuminuria, irrespective of treatment sequence. Residual geometric mean albuminuria with baseline treatment was 711 mg per day (95% CI 485–1043); it was significantly reduced by sodium restriction (393 mg per day [258–599], p=0·0002), by hydrochlorothiazide (434 mg per day [306–618], p=0·0003), and to the greatest extent by their combination (306 mg per day [203–461], p<0·0001). Orthostatic complaints were present in two patients (4%) during baseline treatment, five (11%) during addition of sodium restriction, five (11%) during hydrochlorothiazide treatment, and 12 (27%) during combination treatment. No serious adverse events occurred. We conclude that sodium restriction is an effective non-pharmacological intervention to increase RAAS blockade efficacy in type 2 diabetic nephropathy. None.